2007
DOI: 10.1088/0034-4885/70/11/r04
|View full text |Cite
|
Sign up to set email alerts
|

Test of some fundamental principles in physics via quantum interference with neutrons and photons

Abstract: The limitations and possibilities that the concept of quantum interference offers as a tool for testing fundamental physics are explored here. The use of neutron interference as an instrument to confront against measurement readouts some of the principles behind metric theories of gravity will be analyzed, as well as some discrepancies between theory and experiment. The main restrictions that this model embodies for the study of some of the features of the structure of space-time will be explicitly pointed out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 165 publications
(441 reference statements)
0
6
0
Order By: Relevance
“…The GUP effects have been studied on condensed, atomic matter, black holes at LHC [44][45][46], the Liouville theorem (LT), and the weak equivalence principle (WEP) [47]. Also, the small observed violations of the WEP in experiments of neutron interferometry can be explained using GUP [48][49][50].…”
Section: Generalized Uncertainty Principle (Gup)mentioning
confidence: 99%
“…The GUP effects have been studied on condensed, atomic matter, black holes at LHC [44][45][46], the Liouville theorem (LT), and the weak equivalence principle (WEP) [47]. Also, the small observed violations of the WEP in experiments of neutron interferometry can be explained using GUP [48][49][50].…”
Section: Generalized Uncertainty Principle (Gup)mentioning
confidence: 99%
“…( 10.5) and to the masses of hypothetical exchanged particles. Comprehensive reviews on this topic have been given by Adelberger et al (2003), Camacho andCamacho-Galvan (2007), andAntoniadis et al (2011). They urged new investigations with neutrons for the gravitational force at small distances (1-10 μm).…”
Section: Non-newtonian Gravity Effects 313mentioning
confidence: 99%
“… gives a positive contribution to the pressure. As discussed in [12], the exact bound state on  can be obtained by comparing with observations and experiments [16]. The gamma rays burst would allow us to set an upper value for the GUP-charactering parameter  .…”
Section: Comparison To Lattice Qcd Simulations With Massless Quarksmentioning
confidence: 99%
“…In a series of earlier papers, the effects of GUP was investigated on atomic and condensed matter systems [2,[6][7][8], on the weak equivalence principle (WEP), and on the Liouville theorem (LT) in statistical mechanics [9]. For instance, it has been found that GUP can potentially explain the small observed violations of the WEP in neutron interferometry experiments [10][11][12]. Also, it can predict the existence of a modified invariant phase space which is relevant to the Liouville theorem.It seems that this approach accordingly modifies almost all mechanical Hamiltonians.…”
mentioning
confidence: 99%